Sensory substitution and augmentation techniques in cerebral visual impairment: a discussion of lived experiences - Duesing, Stephanie L.; Lane-Karnas, Katie; Duesing, Sebastian James Adam; Lane-Karnas, Mae; Y, Nai; Chandna, Arvind (Frontiers in Human Neuroscience, 2025)
Pediatric vision loss due to cerebral visual impairment (CVI) is an urgent public health issue, demanding evidence-based (re)habilitation and educational strategies. As with other neurodiverse populations, research on CVI needs to be directly informed by the lived experiences of those affected—children, adults, and their families. In this paper, three individuals with early-onset CVI and two parents discuss sensory substitution and augmentation developed in childhood in the absence of early identification of CVI, and they detail the important impact of the empowering, professionally taught non-visual skills–such as braille, orientation and mobility training, and assistive technology–which were acquired later. Efforts to improve visual perception ability and understanding of the visual world, both effective and ineffective, were made through traditional, professionally administered vision therapy, self-taught coping strategies, and from intensive arts participation. The authors discuss the strategies they use to leverage senses other than vision to achieve their daily life, educational, social, and career goals. Nonvisual skills training effective in those with ocular blindness, though received later in life after the delayed diagnosis, proved to be indispensable for these authors’ who have CVI access to all aspects of independent life. It is our hope that these personal experiences may encourage research into how traditional nonvisual skills training used for the ocularly blind, as well as sensory substitution and augmentation techniques, may be used to develop evidence-based multidisciplinary interventions; improved academic and independent life skills; multisensory educational and therapeutic interventions; and successful integration into the community for all CVIers.